Big band, small town: the strengthening of music education in rural schools through performance and community service - Smallwood, Kirsten Miranda Votaw (My University, 2025)
The project and subsequent lessons demonstrated in this report are focused on the impact community service has upon band programs in rural schools. The goal of this project was to present an opportunity for the jazz band students to not only add performance hours, but to also give back to the community that supports through many different avenues. As a result of this endeavor, my students gained skills musically, as well as those skills needed to efficiently lead and communicate with each other and effectively plan an event on their own. This project was based on the knowledge and skills that I gained in the summer masters’ program, and more specifically in Learning Theories in Music Teaching. Through this project, the summer Masters’ program pushed me to get out of my comfort zone and approach performance as service and connect my students to the community. Over the course of my Masters’ Program, I have been able to discover and refine my own philosophy of music education as well as fine tune it to fit the specific needs of my students in my current teaching situation. I have learned how to approach the podium in a different light through score analysis and rehearsal techniques, while also seeing myself as the educator as someone who is a guide in students’ learning rather than a boss. I have found what works best for my students, and how to effectively apply those different methods. The high standard of excellence set forth by my professors in the summer Masters’ program has aided in my endeavor to continue to hold my students to a high standard of achievement as well as realize what effects music has on their lives and why they continue to perform.
Keywords: Music education; Rural music education; Jazz education